ANALISIS KEBIJAKAN FULL DAY SCHOOL DALAM MEMBENTUK KARAKTER SISWA - Andi Sarima; Jusma Jusma; Ramlah Ramlah (JURNAL MAPPESONA, 2020)
Character is very important for students. One effort of qualified students’ character building is by religion-based school and implement full day school system that continuously character building can be reached. This study is aimed to know: (1) the implementation of full day school in students’ character building, (2) constraints in implementing full day schoolin students’ character building. The research method used in this study is a qualitative method with a descriptive approach to the study of qualitative. Result of this study shows that: (1) The implementation of full day school is conducted a day full in order to develop the students’ character building process is conducted through cultural practice in school such as routine activities, spontaneous activities and character building method. Students character building also developed through extracurriculars. (2) Constraints in implementing full day school in students’ character building is students’ awareness, the less of support and appreciation from parents or students’ custody, and available facilities.